Income Tax Revenue Elasticities with Endogenous Labour Supply - John Creedy; Norman Gemmell (New Zealand Government, The Treasury, 2002)
It is important for the design of tax policy to be able to measure reliably the income elasticity of tax revenue. This gives the extent to which tax revenues change as a result of a change in earnings. Analytical expressions for income tax revenue elasticities treat earnings as exogenous, so that they do not accommodate the endogenous response of labour supply to the income tax system. This paper shows how these expression can be adapted to allow for endogenous labour supply. It identifies how far, and in what circumstances, labour supply effects are quantitatively important for revenue responsiveness estimates, both for individual taxpayers and in aggregate. It is shown that even a relatively simple tax-benefit structure can produce labour supply responses which considerably alter tax revenue elasticity calculations. It is shown that , even with modest leisure preferences, tax-wage elasticities are significantly higher that tax-income elasticities.
Keywords: H24; H31; J22; 330; Income Taxation; Revenue; Elasticity; Labour Supply